Using a visual support package to facilitate independent leisure engagement and choice-making for individuals with moderate to severe autism in Taiwan - Shan, Ge; Wang, Hui-Ting; Juan, Chen-Ya; Chang, Chien-Huey (Autism : the international journal of research and practice, 2024)
Self-determination is a complex process with several components, such as making choices and independence. However, limited research on self-determination has focused on individuals with moderate to severe autism spectrum disorder. This study aimed to support independent leisure engagement and choice-making of leisure activities for this population by using a visual support intervention package, including the use of a visual activity schedule, video modeling, structured environment, preference assessment, and prompt procedures. The study used a single case research multiple baseline probe design to test the effectiveness of the intervention on three adults with autism spectrum disorder. Findings showed that implementing the visual support package was effective in promoting independent leisure engagement and facilitating choice-making of leisure activities. The study highlights the need for and advantages of incorporating video modeling and preference assessment into the visual activity schedule for this particular population. Lay Abstract Self-determination encompasses various components, including decision-making and independence, making it a complex process. While the importance of self-determination for individuals with autism spectrum disorder has been explored in previous studies, there is limited research focusing on individuals with moderate to severe autism spectrum disorder. Evidence-based practices such as visual activity schedules and video modeling have shown effectiveness in promoting independence among individuals with autism spectrum disorder. To address the need for independence and choice-making among individuals with moderate to severe autism spectrum disorder, this study developed a visual support package incorporating visual activity schedules, video modeling, preference assessments, and prompt procedures. By investigating the intervention’s effectiveness in three participants, this study contributes to the existing literature on the use of a visual activity schedule and video modeling in enhancing choice-making and independent leisure engagement. Following the intervention, all participants were able to select three leisure activities, develop their own visual schedules, and complete them. Notably, this study conducted preference assessments to determine participants’ preferred leisure activities and did not provide additional reinforcement. Practical implications of this research include incorporating video prompting as needed and adjusting activity engagement time. Future research should explore the long-term effectiveness of the visual support package and its application in developing novel skills or vocational activities for individuals with moderate to severe autism spectrum disorder. This study fills a critical gap in the literature, providing important insights for practices and research in the field of autism spectrum disorder interventions.